Benign Bilateral Adenomyoepithelioma of the Mammary Gland in a Ring-tailed Lemur (Lemur catta). Issue 2 (August 2017) - Suárez-Bonnet, A.; Grau-Bassas, E. Rodríguez; Herráez, P.; Quesada-Canales, O.; Priestnall, S.L.; de los Monteros, A. Espinosa
Summary: Naturally occurring mammary tumours are uncommon in prosimians. A 20-year-old female ring-tailed lemur ( Lemur catta ) developed bilateral enlargement of the mammary glands. Surgical removal revealed that both masses were comprised of multiple nodules and cystic areas that entirely replaced the normal glands. Histologically, a benign neoplastic biphasic cellular proliferation, composed of luminal–epithelial and basal–myoepithelial components, was identified. Immunohistochemical analysis for expression of cytokeratin (CK) AE1/AE3, CK7, CK5 + 8, CK14, vimentin, p63 and 14-3-3σ highlighted the biphasic nature of the neoplasm. A low mitotic count, low Ki67 labelling index, expression of oestrogen receptor-α, lack of expression of human epidermal growth factor receptor and a 3-year disease-free period without recurrence supported the benign nature of the tumour. Macroscopically, histologically and immunohistochemically this neoplasm resembled benign adenomyoepithelioma of the breast in women. This is the first complete report of a naturally occurring mammary tumour in a ring-tailed lemur.